The Validity of Spatial Ability Test Instrument At Primary Level Based on Classical Test Theory - Fardiana, Rina; Kartono, Kartono; Ridlo, Saiful (Universitas Negeri Semarang, 2024)
Spatial ability is part of the learning outcomes for the geometry element of the Merdeka Curriculum. The spatial ability assessment instrument must be proven valid so that it can be ensured that it correctly measures the aspect it wants to measure. This research developed and proved the validity of an instrument for assessing the spatial ability of phase C students in grade V based on classical test theory. The instrument was validated by 6 raters consisting of 3 assessment expert and 3 mathematics teachers. The results of the 6 raters' assessments were processed using Aiken V. The results showed that each question item was proven to be content valid. The 20 question items were in accordance with the indicators, material coverage and constructs as measured by a calculated V value of not less than 0.92. The instrument was tested on 40 grade V students at SDN 04 Petang Kalideres to prove the construct validity. The test results showed that 14 of the 20 questions were proven to be valid with r value of more than 0.308, 1 out of 6 questions should be eliminated due to a negative r value while the other 5 questions should be revised, and the instrument reliability was 0.659 in the medium category